Ear-tip bloodletting therapy combined with external application of Traditional Chinese Medicine in treating hordeolum at the early stage in a child and related nursing management (耳尖放血联合中药外敷治疗1例早期麦粒肿患儿的护理体会) - LIU Hongyan (刘红艳); YIN Keqin (尹可欣); CHEN Xiangping (陈香平); TANG Ling (唐玲); LI Jinhuan (李金环); DUAN Yixuan (段怡璇) (中西医结合护理)
This paper observed the effect of ear-tip bloodletting therapy combined with external application of Traditional Chinese Medicine (TCM) in treating hordeolum at the early stage in a child, and summarized related nursing measures during the treatment. Key issues of ear-tip bloodletting therapy, TCM external application emotional care and diet intervention were mentioned. The ear-tip bloodletting therapy combined with TCM external application is effective to relieve the hordeolum associated symptoms and improve the rehabilitation of the patient. (本文总结耳尖放血联合中药外敷治疗1例小儿早期麦粒肿的护理经验, 包括耳尖放血的操作方法、中药局部外敷以及情志、饮食等常规护理等。通过经络刺激和中药湿敷, 耳尖放血联合中药外敷能有效缓解患儿麦粒肿症状, 促进疾病康复。)